Pediatric endoscopic retrograde pancreatography expertise in chronic pancreatitis: a single-center analysis - Guo, Hongxi; Luo, Juan; Yang, Hu; Yang, Jun; Bian, Hongqiang; Duan, Xufei; Wang, Xin (Frontiers in Pediatrics, 2025)
Background and aimChronic pancreatitis (CP) in children has exhibited an annual increase in incidence in recent years. Pediatric CP presents unique clinical features compared to adult cases. Endoscopic retrograde pancreatography (ERP) serves as a valuable and safe tool for diagnosing and treating CP in adults. However, data on endoscopic treatment of CP in children are still limited.MethodsDemographics, etiology, surgical indications, diagnosis, treatment details, associated complications, and follow-up information were retrospectively studied in consecutive patients (<18 years old) who underwent ERP for CP between January 2020 and October 2024.ResultsA total of 17 children (7 male, 10 female) with a mean age of 10.0 ± 2.7 years were included in the study. A total of 34 endoscopic treatments were conducted. Recurrent abdominal pain was the primary clinical symptom. Imaging predominantly revealed pancreatic duct abnormalities such as tortuous dilatation and the presence of pancreatic duct stones. Notably, 41.2% (7 cases) involved genetic and congenital anatomical variations. Pancreatic duct stent placement was successfully performed in all 17 children (100.0% success rate). Stent replacements occurred on average 2.2 times (range 1–5) at intervals of 3–6 months. Postoperative pancreatitis developed in 2 cases (5.9%, 2/34), and hyperamylasemia occurred in 5 cases (14.7%, 5/34). The postprocedure visual analogue scale (VAS) score for abdominal pain significantly decreased from 6 to 1 (P < 0.001). The annual frequency of pancreatitis episodes showed a significant reduction, decreasing from 2.4 times pre-treatment to 0.6 times post-treatment (P < 0.05). Body mass index (BMI) also showed a significant improvement post-treatment compared to pre-treatment (P < 0.05).ConclusionsERP performed by trained endoscopists utilizing standard adult endoscopes and accessories proved a safe and effective treatment option for pediatric CP, with complication rates comparable to those reported in adult cases.